Reading Marechera - Hamilton, Grant; Cambridge eBooks (Suffolk : Boydell & Brewer, 2013)
Considered one of Africa's most innovative and subversive writers, the Zimbabwean novelist, poet, playwright and essayist Dambudzo Marechera is read today as a significant voice in contemporary world literature. Marechera wrote ceaselessly against the status quo, against unqualified ideas, against expectation. He was an intellectual outsider who found comfort only in the company of other free-thinking writers - Shelley, Bakhtin, Apuleius, Fanon, Dostoyevsky, Tutuola. It is this universe of literary thought that one can see written into the fiction of Marechera that this collection of essays sets out to interrogate. In this important and timely contribution to African literary studies, Grant Hamilton has gathered together essays of world-renowned, established, and young academics from Africa, Europe, Asia and Australia in order to discuss the important literary and philosophical influences that course through Marechera's prose, poetry and drama. From classical allusion to the political philosophy of anarchism, this collection of new research on Marechera's work makes clear the extraordinary breadth and quality of thought that Marechera brought to his writing. Grant Hamilton is Assistant Professor of English Literature at the Chinese University of Hong Kong. He is the author of 'On Representation: Deleuze and Coetzee on the Colonized Subject' (Rodopi, 2011), as well as a number of articles on contemporary African, postcolonial, and world literatures. He is currently working on his second book, 'Deleuze and African Literature'.
Introduction : Marechera & the outside / Grant Hamilton -- A brotherhood of misfits : the literary anarchism of Dambudzo Marechera & Percy Bysshe Shelley / Tinashe Mushakavanhu -- Blowing people's minds : anarchist thought in Dambudzo Marechera's Mindblast / Anias Mutekwa -- Grotesque intimacies : embodiment & the spirit of violence in 'House of hunger' / Anna-Leena Toivanen -- Tracing the stain in Marechera's 'House of hunger' / Grant Hamilton -- Menippean Marechera / Bill Ashcroft -- Black but not Fanon : reading The Black insider / David Huddart -- The avant-garde power of Black sunlight : radical recontextualizations of Marechera from Darius James to China Miéville / Mark P. Williams -- Classical allusion in Marechera's prose works / Madhlozi Moyo -- Revisiting 'The servants' ball' / Memory Chirere -- Marechera, the tree-poem artifact / Eddie Tay.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Marechera, Dambudzo -- Criticism and interpretation; Zimbabwean literature (English) -- History and criticism; Anarchism in literature; Electronic books